In vitro antiproliferative and cytotoxic activities of novel triphenyltin isoselenocyanate in human breast carcinoma cell lines MCF 7 and MDA-MB-231 - Hunakova, Luba; Horvathova, Eva; Matuskova, Miroslava; Bobal, Pavel; Otevrel, Jan; Brtko, Julius (Medical oncology (Northwood, London, England), 2022)
Intensive investigation for novel antiproliferative and cytotoxic effective chemical compounds is currently concentrated on structurally modified agents of natural or synthetic source. The selenium derivative of triorganotin compound, triphenyltin isoselenocyanate (TPT-NCSe) caused higher cytotoxicity in hormone sensitive MCF 7 (IC 50-250 nM) in comparison with triple-negative MDA-MB-231 breast carcinoma cell line (IC 50-450 nM) as determined by MTT assay. Measurement of DNA damage showed presence of crosslinks in both cell lines treated by increasing TPT-NCSe concentrations. This compound decreased mitochondrial membrane potential shown by JC-1 staining in a concentration-dependent manner in both cell lines. Activation of caspases-3/7 was observed in MDA-MB-231 cells and was significant only by concentrations causing significant level of crosslinks. On the other hand, migration assay revealed inhibitory effect of viability keeping 100 nM concentration of TPT-NCSe on migration of MDA-MB-231 cells. Our data has shown that this selenium containing triorganotin molecule exerts DNA damage-linked antineoplastic activity in breast carcinoma cell lines studied.
Keywords: nádory prsu; Selenium; Cell Proliferation; organocínové sloučeniny; protinádorové látky; Organotin Compounds; Migration; Humans; triple-negativní karcinom prsu; Cytotoxicity; Antineoplastic Agents; Triple Negative Breast Neoplasms; Female; organoselenové sloučeniny; MFC-7 buňky; proliferace buněk; Organoselenium Compounds; Breast cancer; DNA crosslinks; ženské pohlaví; selen; Cell Line, Tumor; nádorové buněčné linie; apoptóza; Triorganotin isoselenocyanates; MCF-7 Cells; lidé; Apoptosis; Breast Neoplasms